Si-rhodamine fluorescent probe for monitoring of hypochlorous acid in the brains of mice afflicted with neuroinflammation. Issue 10 (17th January 2023) - Liang, Fanghui; Jiang, Jian; Yang, Xinyue; Zhang, Guoyang; Zhou, Jiaying; Han, Jiahao; Geng, Yujie; Wang, Zhuo
Abstract : The fluorescent probe SiR-FH realized real-time monitoring of HClO in the brains of mice with LPS-induced neuroinflammation. Abstract : Neuroinflammation leads to a persistent oxidative stress in the brain, and is closely related to the pathology of various neurological disorders. Hypochlorous acid (HClO) is a reactive oxygen species (ROS) that, at high levels, can cause brain tissue damage and neurogenic apoptosis. Herein, we designed and synthesized a silicon-rhodamine (SiR)-based formohydrazide (FH)-containing fluorescent probe, denoted as SiR-FH, for sensing HClO. This probe showed good selectivity, rapid response and high sensitivity. SiR-FH was successfully used to detect endogenous and exogenous HClO in living cells. Moreover, SiR-FH realized real-time monitoring of change in HClO flux in the brains of mice with LPS-induced neuroinflammation. The probe provides a practical tool for the monitoring of oxidative stress related to neuroinflammation.